A Development on Air Pollution Detection Sensors based on NB-IoT Network for Smart Cities - Duangsuwan, Sarun; Takarn, Aekarong; Jamjareegulgarn, Punyawi (My University, 2018)
Currently, air pollution is a big problem for people health in cities that suffered from the more factors such as the traffic, industrial, or forest fire or polluted skies. This paper presents a development of air pollution detection sensors and monitoring for smart city, Thailand 4.0. The development is designed by using five standard sensors such as carbon dioxide: CO, ozone: O 3 , particulate matter: PM 10 , nitrogen dioxide: NO 2 , and sulfur dioxide: SO 2 respectively, and web monitor shows the graph of the air quality index (AQI). To monitor the air quality, the data processing is computed by using Arduno MEGA 2560 and Respberri Pi 3 to connect with Narrowband Internet of Things (NB-IoT) module network. Experimental setup, the measurement location is examined at Sai Mai District, Bangkok. As the result, we found that the AQI level of measured location is good air quality. We emphasize that the monitoring of air pollution in smart cities is very important.
Keywords: Air pollution; NB-IoT; smart city; smart sensors